New evidence for diet and subsistence economy in Early and Middle Bronze Age Cyprus. (October 2020) - Scirè-Calabrisotto, Caterina; Webb, Jennifer M.; Frankel, David; Ricci, Paola; Altieri, Simona; Lubritto, Carmine
Highlights: Animal data provide the first isotopic baseline for Early/Middle Bronze Age Cyprus. Animal data indicate exploitation of a mainly C3 ecosystem. Cattle and caprines were possibly subjected to different herding practices. Human data suggest a primarily C3 terrestrial protein-based diet. Abstract: Stable carbon and nitrogen isotope data from the settlement of Marki Alonia provides new evidence for dietary patterns and aspects of livestock management during the Early and Middle Cypriot Bronze Age. Animal data indicate exploitation of a mainly C3 ecosystem and hint at the possibility that caprines and cattle were subjected to different herding practices; they currently constitute the sole available isotopic baseline for this region and time period. As for the few analysed humans, a primarily C3 terrestrial protein-based diet can be suggested.